Kornerupine in Mg-Al-rich gneisses from Namaqualand, South Africa: mineralogy and evidence for late-metamorphic fluid activity - Waters, D; Moore, J (1985)
Three kornerupine occurrences are reported in distinctive SiO-poor, MgO- and AlO-rich paragneisses from the Namaqualand Metamorphic Complex in South Africa. Kornerupine coexists stably with phlogopite, cordierite, orthopyroxene, gedrite, sapphirine, sillimanite and plagioclase and, in sapphirine-free rocks, with spinel and corundum. Tourmaline of a texturally older generation than kornerupine is commonly present in the same samples. Ten analysed kornerupines show a variation in total Fe as FeO from 1.8 to 10.9 weight per cent. BO contents are estimated from x-ray data and a few spectrochemical analyses to range from 0.9 to 3.5 weight per cent. There is a strong inverse correlation between B and Al. Total iron content has a strong and systematic effect on refractive index, colour and dispersion. Fe and Mg are systematically partitioned with the other minerals, and Mg/(Mg+Fe) ratios increase as follows: spinel